Father of liberty : Jonathan Mayhew and the principles of the American Revolution - Mullins, Patrick (American political thought., 2017)
Dr. Jonathan Mayhew was the most politically influential clergyman in eighteenth-century America; he championed the principles of natural rights, constitutionalism, and resistance to tyranny in press and pulpit from 1750 to 1766. He did more than any other clergyman to prepare New England for disobedience to British authority in the 1760s.